Aerobic Bacterial Community of American Cockroach Periplaneta americana,a Step toward Finding Suitable Paratransgenesis Candidates - Sanaz Akbari; MohammadAli Oshaghi; SaedehSadat Hashemi-Aghdam; Sara Hajikhani; Ghazaleh Oshaghi; MohammadHasan Shirazi (Tehran University of Medical Sciences, 2015)
Background: Cockroaches mechanically spread pathogenic agents, however, little is known about their gut microbiota. Identification of midgut microbial community helps targeting novel biological control strategies such as paratransgenesis. Here the bacterial microbiota of Periplaneta americana midgut, were identified and evaluated for finding proper paratransgenesis candidate. Methods: Midgut of specimens were dissected and cultivated in different media. The bacterial isolates were then identified using the phenotypic and 16S-rRNA sequencing methods. Results: The analytical profile index (API) kit showed presence of 11 bacterial species including: Escherichia coli, Shigella flexineri, Citrobacter freundii, E. vulneris, Enterobacter cloacae, Yersinia pseudotuberculosis, Y. intermedia, Leclericia adecarboxylata, Klebsiella oxytoca, K. planticola, and Rahnella aquatilis in the cockroach midguts. The first three species are potentially symbiotic whereas others are transient. The conventional plating method revealed presence of only four isolates of Salmonella, E. coli, and Proteus which in three cases mismatched with API and 16S-rRNA genotyping. The API correctly identified the four isolates as Shigella flexneri, Citrobacter freundii, and E. coli (n= 2). 16S-rRNA sequence analysis confirmed the API results; however the C. freundii sequence was identical with C. murliniae indicating lack of genetic variation in the gene between these two closely related species. Conclusion: A low number of potentially symbiotic bacteria were found in the American cockroach midguts. Among them Enterobacter cloacae is a potential candidate for paratransgenesis approach whereas other bacteria are pathogens and are not useful for the approach. Data analysis showed that identification levels increase from the conventional to API and to genotyping respectively.